Sustainable Strategies for Halal Tourism Infrastructure in the Digital Age: Integrating Architecture, Urban Planning, and Technology - Chantarungsri, Chariyada; Alam, Azhar (Universitas Muhammadiyah Surakarta, 2024)
This study investigates sustainable strategies for halal tourism infrastructure in urban areas, addressing the growing demand for halal-compliant travel options among the Muslim population. The purpose of this research is to explore the integration of Islamic principles with sustainable practices, focusing on halal compliance, environmental design considerations, and community engagement. A systematic review of 96 academic publications from 2017 to 2024 was conducted, utilizing databases such as Scopus and Web of Science to analyze the intersection of architectural design, urban planning, and technological advancements in halal tourism. The findings reveal that halal compliance is essential for enhancing the travel experience and building trust within the halal tourism market. Additionally, sustainable practices rooted in Islamic values can mitigate the environmental impacts of mass tourism while promoting cultural sensitivity and economic viability. The study highlights the importance of community involvement and effective stakeholder collaboration in developing halal tourism infrastructure. This article contributes valuable insights for policymakers and industry professionals, emphasizing the need for adaptable frameworks that accommodate diverse urban contexts and promote inclusivity. The integration of technology, including smart solutions and standardized certification processes, is identified as crucial for enhancing halal tourism management. Ultimately, this study underscores the potential of sustainable urban halal tourism to serve as a model for responsible and culturally sensitive tourism development worldwide.